Atividade econômica e inovação na indústria brasileira: uma análise com dados em painel (2010-2016) - Freire, Débora; Montenegro, Rosa Lívia Gonçalves; Resende, Marco Flávio da Cunha; Libânio, Gilberto (Brazilian Keynesian Review, 2020)
The aim of the present work is to analyze the relationship between the level of economic activity and technological innovation in Brazilian industry from 2010 to 2016. The central hypothesis of the paper is that the greater the economic activity, the higher the positive impact on the innovation rate, through channels such as the increase in investments in fixed capital and the improvement in the financing conditions for innovation activities. The analysis is based on a database of the first six years of the survey called Innovation Survey in which it was possible to obtain a panel segmented by four blocks of industrial sectors. These data were analyzed by means of panel data regression model that reveals the temporal evolution of the relation between the level of industrial activity and the rate of innovation of firms. The main result suggests that the overcoming of the current crisis and the consequent recovery of economic activity are important elements for the increase of innovation rates in the Brazilian industry.